Evaluation of Regional Policy Regarding Street Vendors: A Case Study of Bone Regency from the Perspective of Siyasah Syar’iyyah - Sattuo, Muhammad; Maskawati, Maskawati; Fathi Aboalela, Nahi Hashim (IAIN Bone, 2025)
This study evaluates the implementation of Regional Regulation No. 1 of 2020 in Bone Regency, focusing on the consistency between legal provisions, field practices, and normative justice principles. Adopting a juridical-empirical approach, the research integrates normative legal analysis with interviews and field observations of street vendors (PKL). The findings indicate that despite formal regulations on zoning, operational hours, and empowerment, implementation is hindered by weak enforcement, limited awareness of legal norms among vendors, and minimal stakeholder participation. These gaps result in tensions between local policy objectives and constitutional guarantees, particularly the right to work and livelihood. From the perspective of Siyasah Syar’iyyah, the policy lacks full alignment with the principles of al-maslahah al-‘ammah, distributive justice, and the protection of vulnerable groups. This study contributes an integrative legal-ethical framework, bridging positive law with Islamic values, and recommends a participatory governance model to enhance legal legitimacy and social justice in informal sector regulation.